A chipless swaging forming process for screw tip
By using a water-based lubricating composition to form a semi-solid pre-coated film through high-frequency induction heating and air knife blowing, the problems of low material utilization and lubricant loss in screw tail drill tip forming are solved, achieving chipless rotary forging and improved surface finish, which is suitable for the fastener manufacturing and processing field.
Patent Information
- Application Number
- CN202610504649.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-08-25
AI Technical Summary
In the existing screw tail drill tip forming process, the material utilization rate of the cutting process is low, while the chipless rotary forging process faces the problem that conventional liquid lubricant is easily squeezed out and lost, resulting in forming defects. In addition, high viscosity or solid lubricant is difficult to clean and affects subsequent processes.
A water-based lubricating composition is used in conjunction with high-frequency induction heating and air knife blowing to form a semi-solid pre-coated film. By providing continuous extreme pressure lubrication in the rotary forging process, a high-viscosity film layer is formed by the chemical reaction of components such as boric acid powder, D-tartaric acid and polyethylene glycol, which prevents lubricant loss and maintains surface cleanliness during the cleaning process.
It extends the service life of rotary forging dies, improves the surface finish of screw drill tips, achieves chip-free rotary forging, improves material utilization and mechanical properties after forming, and facilitates cleaning and electroplating in subsequent processes.
Smart Images

Figure CN122625569A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fastener manufacturing and processing technology, specifically to a chipless rotary forging process for the drill tip of a screw tail. Background Technology
[0002] Screws with drill tips are widely used in construction and machinery assembly. The conventional method for machining the drill tip is cutting. The cutting process removes excess metal with a cutting tool to create the drill tip shape. This process generates a large amount of metal debris, resulting in low raw material utilization and increased processing costs.
[0003] To address the issue of material waste, chipless rotary forging has been increasingly applied to drill tip forming. Rotary forging relies on a die to perform high-frequency radial forging of metal wire, forcing the metal to undergo plastic flow and elongation. However, under the high-frequency, intense deformation conditions of rotary forging, the interface between the die and the metal wire generates high contact stress and frictional heat. When using conventional liquid lubrication, the lubricant is easily lost due to mechanical compression as the metal wire enters the pressure zone of the die, making it difficult to maintain a complete lubricating film in the core deformation area. This lubrication failure causes direct contact between the die and the metal substrate, accelerating die wear and causing localized damage to the workpiece surface, such as roughening, surface burning, and jamming.
[0004] To address the issue of liquid lubricants easily leaking out, some production processes have switched to high-viscosity oil-based lubricants or added solid lubricating powders such as graphite and molybdenum disulfide. However, this has led to technical challenges in post-processing cleaning. High-viscosity oil-based media or solid powders typically cannot be completely removed by conventional environmentally friendly water-based cleaning processes. Hydrophobic substances or inorganic components adhering to the workpiece surface are prone to solidification or carbonization during subsequent high-temperature heat treatment processes. This not only reduces the surface cleanliness of the product but also severely affects the adhesion of subsequent electroplated layers. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a chipless rotary forging process for screw tail drill tips. This process solves the problems of low material utilization in existing screw tail drill tip forming processes, and the challenges faced by conventional liquid lubricants, such as easy extrusion and loss leading to forming defects, and the difficulty in cleaning high-viscosity or solid lubricants, which can affect subsequent processes.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A chipless rotary forging process for the drill tip of a screw tail includes the following steps:
[0008] Deionized water was heated, boric acid powder and D-tartaric acid were added, and the mixture was stirred at a constant temperature. Polyethylene glycol and water-soluble tribochemical extreme pressure agent were added, and the stirring speed was increased to perform shear mixing. Triethanolamine was added dropwise under continuous stirring until the pH of the solution stabilized. The mixture was then kept warm and allowed to stand to obtain a water-based lubricating composition.
[0009] The metal wire with the surface oxide scale removed is cleaned in an ultrasonic cleaning tank and then sent to the rotary forging machine.
[0010] The water-based lubricating composition is preheated and then sprayed onto the surface of the moving metal wire through an array of atomizing nozzles.
[0011] The metal wire passes through a high-frequency induction heating coil to heat the surface of the metal wire, and an annular air knife located at the outlet of the high-frequency induction heating coil blows across the surface of the metal wire to form a high-viscosity semi-solid pre-coated film on the surface of the metal wire.
[0012] The metal wire pre-coated with the high-viscosity semi-solid pre-coated film enters the rotary forging die of the rotary forging machine and is rotary forged to form a screw tail drill tip structure.
[0013] The screw tail drill tip structure after rotary forging is cooled down, cleaned in a weakly alkaline water-based cleaning agent, rinsed and dried with hot air.
[0014] By adopting the above technical solution, a semi-solid pre-coated film is formed by using a water-based formula in combination with high-frequency induction heating and air knife blowing, and continuous extreme pressure lubrication is provided in the rotary forging process. Therefore, the effects of extending the service life of rotary forging dies, improving the surface finish of screw drill tips, and achieving chip-free rotary forging are achieved.
[0015] The specific reaction mechanism and innovative process are explained in detail below:
[0016] Step 1: Lubricant Complexation Stage. Boric acid powder itself has a layered crystalline structure, which reduces the coefficient of friction through interlayer shear slip during plastic deformation of the metal. D-tartaric acid has multiple carboxyl and hydroxyl functional groups, which undergo coordination complexation reactions with iron atoms on the metal surface, dissolving and removing residual oxides on the metal surface, while simultaneously forming a chemical adhesion on the metal substrate. Polyethylene glycol provides the basic fluid viscosity, and triethanolamine adjusts the pH of the system to maintain a weakly alkaline environment, preventing oxidation and corrosion of the metal wire before processing.
[0017] Step two, film formation and concentration stage. After the water-based lubricating composition is applied to the surface of the metal wire in a mist form, a high-frequency induction heating coil generates eddy current heat on the surface of the metal wire using the principle of electromagnetic induction. The heat is conducted from the inside to the outside, causing the free water in the lubricating composition to vaporize rapidly. The annular air knife located at the outlet provides a high-speed directional compressed airflow, stripping away the vaporized water vapor on the surface and promoting the aggregation and entanglement of polyethylene glycol molecular chains. After the water is removed, the system undergoes a phase change and concentration, encapsulating boric acid and water-soluble tribochemical extreme pressure agents, and solidifying on the surface of the metal wire to form a high-viscosity semi-solid pre-coated film. This film layer has structural strength, overcoming the defect of liquid lubricant being lost due to mechanical extrusion at the entrance of the rotary forging die, ensuring that the surface has sufficient lubricating medium when entering the forming zone.
[0018] Step 3: Tribochemical Reaction Forming Stage. During high-frequency radial forging of the metal wire using a rotary forging die, localized high temperatures and contact stresses are generated at the contact interface. The semi-solid pre-coated film undergoes plastic elongation synchronously with the metal substrate. Under high temperature and high pressure, the water-soluble tribochemical extreme pressure agent undergoes a tribochemical reaction, and the functional groups containing active phosphate groups chemically bond with the iron metal matrix, generating a chemical conversion film of iron phosphate with low shear strength. This conversion film acts as a physical isolation barrier, preventing cold welding adhesion between the metal wire and the die, and ensuring that the metal grains complete the cutting-free drill tip forming under plastic flow.
[0019] Preferably, in the step of obtaining the water-based lubricating composition, the deionized water is heated to 45°C to 50°C; the added boric acid powder accounts for 5.0% to 8.0% of the total mass of the water-based lubricating composition, and the added D-tartaric acid accounts for 1.5% to 2.0% of the total mass of the water-based lubricating composition; the constant temperature stirring time is 30 to 45 minutes, and the constant temperature stirring speed is set to 150 rpm to 200 rpm; the added polyethylene glycol accounts for 15.0% to 20.0% of the total mass of the water-based lubricating composition, and the added water-soluble tribochemical extreme pressure agent accounts for 3.0% to 5.0% of the total mass of the water-based lubricating composition; the shear mixing time is 20 to 30 minutes, and the stirring speed is increased to 300 rpm to 400 rpm; the pH value of the solution is stabilized at 8.2 to 8.5; and the temperature holding and standing time is 15 to 30 minutes.
[0020] By adopting the above technical solution and rationally proportioning the concentrations of each component and the mixing process, it is ensured that boric acid and D-tartaric acid reach a solubility equilibrium state within the temperature range of 45℃ to 50℃. Increasing the stirring speed for shear mixing utilizes mechanical shear force to break down the molecular clusters of the water-soluble tribochemical extreme pressure agent, allowing it to be uniformly dispersed in the polyethylene glycol phase. This ensures that the final high-viscosity semi-solid pre-coated film has a uniform component distribution. Maintaining a stable pH value of 8.2–8.5 helps maintain the stability of the salt structure of the water-soluble tribochemical extreme pressure agent, preventing its free precipitation under acidic conditions.
[0021] Preferably, the preparation steps of the water-soluble tribochemical extreme pressure agent include: heating 3.0 mol equivalents of isotridecyl alcohol polyoxyethylene ether with an average ethylene oxide addition number of 3 to 60°C to 70°C, adding 1.0 mol equivalents of phosphorus pentoxide in batches under nitrogen protection and constant stirring, controlling the reactor temperature within the range of 80°C to 85°C, and maintaining the temperature for 2.5 to 3.0 hours after the addition is complete to obtain the esterification reaction product; adding 2.0% to 3.0% of deionized water by mass to the esterification reaction product, and continuously stirring and hydrolyzing at 70°C to 80°C for 1.0 hour; cooling to 45°C to 50°C, and adding monoethanolamine dropwise until the pH value of the mixed system reaches 6.5 to 7.5.
[0022] By employing the above technical solution, an extreme pressure additive specifically designed for chipless rotary forging environments is synthesized. The synthesis mechanism is as follows: The first step involves a phosphorylation-esterification reaction. The terminal fatty alcohol hydroxyl groups of isotridecyl alcohol polyoxyethylene ether act as nucleophiles, attacking the phosphorus-oxygen bonds in the phosphorus pentoxide molecule, leading to ring opening and generating a mixed product of phosphate monoester and pyrophosphate ester. Nitrogen protection is used to prevent oxidation and discoloration of the reaction system under heating. Batch feeding controls the intense exothermic reaction during esterification, maintaining a stable reactor temperature. The second step involves a hydrolysis reaction. Deionized water, under heating conditions, promotes the breaking and hydrolysis of the pyrophosphate ester bonds in the system, converting the pyrophosphate ester into orthophosphate monoester and orthophosphate diester, which possess surface activity and extreme pressure lubrication properties, reducing the product's viscosity and improving its water solubility. The third step involves a neutralization reaction. Monoethanolamine contains amino basic groups, which undergo a proton transfer reaction with the free acidic hydrogen of the phosphate ester to generate monoethanolamine salts, resulting in an excellent hydrophilic-lipophilic balance and stability in water-based lubricating compositions.
[0023] Preferably, the water-soluble tribochemical extreme pressure agent is an ashless alcohol ether phosphate amine salt; the average molecular weight of the polyethylene glycol is 200-600.
[0024] By adopting the above technical solution, ashless alcohol ether phosphate amine salts can form a chemically adsorbed layer with strong carrying capacity on the metal surface through phosphate ester groups. The amine groups endow the system with good water solubility, and the ashless structure indicates that its molecules do not contain metal cations, so no inorganic ash residue will be generated during subsequent high-temperature cleaning and drying processes. Polyethylene glycol with an average molecular weight of 200-600 is used, whose molecular chain length combines good water-soluble spreading performance with film-forming cohesion after phase change curing.
[0025] Preferably, in the step of sending the metal wire with the surface oxide scale removed to the rotary forging machine after being cleaned in the ultrasonic cleaning tank, the metal wire is selected as 10B21 carbon steel wire or 304 stainless steel wire; the ultrasonic cleaning tank uses deionized water medium, the water temperature is controlled at 40℃~50℃, the ultrasonic frequency is set to 25kHz~40kHz, and the residence time of the metal wire in the ultrasonic cleaning tank is 3~5 seconds; the cleaned metal wire is sent to the rotary forging machine through a roller traction system, and the continuous feed speed is set to 10m / min~15m / min.
[0026] By employing the above technical solution, the cavitation effect generated by ultrasound at 25kHz–40kHz in deionized water is utilized. Cavitation bubbles form and collapse, producing localized microjets. These microjets strip loose particles from the surface of the metal wire and enhance the surface activity of the metal, thereby improving the complexation and adhesion efficiency of D-tartaric acid and extreme pressure agents in the subsequent water-based lubricant composition with the matrix. Controlling the continuous feed rate ensures the consistency of the production cycle and matches it with the subsequent induction heating duration.
[0027] Preferably, in the step of forming the high-viscosity semi-solid pre-coated film, the water-based lubricating composition is preheated to 60°C to 65°C; the atomizing nozzle array is located 15cm to 20cm in front of the inlet of the rotary forging die; and the atomizing gas pressure of the atomizing nozzle array is controlled at 0.2MPa to 0.4MPa.
[0028] By employing the above technical solution, preheating treatment reduces the surface tension of the water-based lubricating composition, and atomized gas pressure disperses it into micron-sized droplets. Spraying at a specified distance can form a fully encapsulated liquid film, providing a uniform material basis for phase change concentration.
[0029] Preferably, in the step of forming the high-viscosity semi-solid pre-coated film, the induction frequency of the high-frequency induction heating coil is 30kHz to 50kHz; the surface layer of the metal wire is heated to 110℃ to 120℃ within 0.5 to 1.0 seconds.
[0030] By adopting the above technical solution and setting the induction frequency to 30kHz–50kHz, the penetration depth of the high-frequency electromagnetic field is controlled to be limited to the surface layer of the metal wire based on the skin effect principle. The surface temperature is raised to 110℃–120℃ within 1.0 second. This provides sufficient heat energy to overcome the latent heat of vaporization of water, achieving rapid drying and dehydration. Simultaneously, it prevents heat from being conducted deep into the wire core, affecting the metallographic mechanical structure of the material, and prevents excessively high temperatures from causing thermal degradation and carbonization of the polyethylene glycol phase.
[0031] Preferably, in the step of forming the high-viscosity semi-solid pre-coated film, the compressed air pressure of the annular air knife is set to 0.3MPa to 0.5MPa, and the airflow direction discharged from the annular air knife forms an angle of 45° to 60° with the forward direction of the metal wire.
[0032] By employing the above technical solution, the high-pressure airflow at a specific angle generates a physical stripping effect, disrupting the gas-liquid balance on the liquid film surface and accelerating the mass transfer and escape of moisture. Simultaneously, the air pressure is used to physically smooth the high-viscosity polyethylene glycol matrix, ensuring a uniform thickness of the high-viscosity semi-solid pre-coated film along the circumference of the metal wire.
[0033] Preferably, in the step of rotary forging the screw tail drill tip structure, the rotary forging die is a four-lobed rotary forging die; the spindle speed of the rotary forging die is set to 300 rpm to 500 rpm; and the radial forging frequency of the rotary forging die on the metal wire is controlled at 2000 to 4000 times / min.
[0034] By adopting the above technical solution, the four-lobed rotary forging die, combined with the set spindle speed and high-frequency forging, transforms the circumferential rotational motion into high-frequency radial impact. The metal wire undergoes grain boundary slip and plastic elongation under multi-axial compressive stress. Because it is always under tri-axial compressive stress, the forming limit of the material is improved, preventing tearing and resulting in a dense internal structure at the drill tip of the formed screw.
[0035] Preferably, in the steps of cleaning in the weakly alkaline water-based cleaning agent, rinsing and hot air drying, the drill tip structure at the screw tail is cooled to below 50°C; the mass fraction of the weakly alkaline water-based cleaning agent is 2% to 3%, and the pH value is 9.0 to 10.0; the cleaning temperature is 50°C to 60°C, and the cleaning time is 3 to 5 minutes; the cleaning method includes soaking and rinsing or spray rinsing.
[0036] By adopting the above technical solution, the film-forming matrix polyethylene glycol of the water-based lubricating composition itself has good water solubility and does not contain hydrophobic components such as mineral oil. Under the action of a weakly alkaline water-based cleaning agent, the residual high-viscosity semi-solid pre-coated film swells and peels off, dissolving in the aqueous medium. Cooling treatment prevents material hardening and deformation caused by thermal stress, and the surface finish after cleaning and dehydration is improved, facilitating subsequent heat treatment and surface electroplating processes.
[0037] This invention provides a chipless rotary forging process for the drill tip of a screw tail. It has the following beneficial effects:
[0038] 1. This invention sprays a water-based lubricating composition onto the surface of a metal wire and uses a high-frequency induction heating coil and annular air knife to rapidly dehydrate and concentrate it, forming a high-viscosity semi-solid pre-coated film before the metal wire enters the rotary forging die. The semi-solid film has high physical strength, avoiding the problem of conventional liquid lubricants being lost in large quantities at the die inlet due to mechanical extrusion. This provides continuous extreme pressure lubrication at the friction interface in the rotary forging process, reduces wear on the rotary forging die, and reduces surface roughening and jamming defects on the metal wire.
[0039] 2. This invention uses a four-lobed rotary forging die to perform high-frequency radial forging of metal wire, causing the metal material to undergo plastic flow under triaxial compressive stress, thereby forming the screw tail drill tip structure. The forming process replaces the traditional cutting process, avoiding the generation of metal chips and improving the material utilization rate of the wire. At the same time, the plastic deformation under triaxial compressive stress can suppress the generation of micro-cracks inside the material, making the internal structure of the screw tail drill tip structure dense and improving the overall mechanical properties.
[0040] 3. The lubricating composition selected in this invention uses polyethylene glycol as a matrix and is compounded with ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt extreme pressure agent. The components have good water solubility and do not contain metal cations. After rotary forging, the residual pre-coated film can be cleaned with a weakly alkaline water-based cleaning agent. The formulation system overcomes the problem of difficult cleaning of traditional oil-based lubricants, and no inorganic ash residue is generated after high-temperature cleaning and drying, which improves the cleanliness of the workpiece surface and is conducive to subsequent heat treatment and surface electroplating processes. Attached Figure Description
[0041] Figure 1 This is a bar chart showing the step comparison between the initial dynamic viscosity and the dynamic viscosity after treatment of the lubricating compositions in each group in Test Example 1 of the present invention;
[0042] Figure 2 This is a comparison chart of the shear yield stress and macroscopic interfacial adhesion level of the film layers after treatment in each group in Test Example 1 of this invention;
[0043] Figure 3 This is a comparison chart of the characteristic endothermic peak temperatures extracted from the gel residues of each group in Test Example 2 of this invention based on DSC analysis;
[0044] Figure 4 This is a comparison chart of the key mass change rates of gel residues extracted from each group based on TGA analysis in Test Example 2 of this invention;
[0045] Figure 5 This is a comparative bar chart showing the total number of qualified screws continuously processed by the rotary forging die under different process conditions in Test Example 3 of this invention;
[0046] Figure 6 This is a comparison chart of the defect rate and macroscopic surface roughness of the finished drill tips in each group in Test Example 4 of this invention;
[0047] Figure 7 This is a comparison chart of the mass of residue per unit area after degreasing and cleaning of the finished products in each group in Test Example 5 of this invention;
[0048] Figure 8 This is a comparison diagram of the surface contact angle of deionized water droplets after cleaning of the finished products in each group in Test Example 5 of this invention. Detailed Implementation
[0049] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings, preparation examples, embodiments, comparative examples, and test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0050] Preparation Examples 1-3:
[0051] Preparation Example 1:
[0052] This preparation example provides a method for preparing a water-soluble tribochemical extreme pressure agent (ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt), comprising the following steps:
[0053] (1) Esterification reaction:
[0054] 3.0 mol equivalents of isotridecyl alcohol polyoxyethylene ether (average ethylene oxide addition number EO=3) were placed in a reaction vessel and heated to 60°C. Under nitrogen protection and constant stirring, 1.0 mol equivalents of phosphorus pentoxide (…) were slowly added in three batches. Control the feeding rate to maintain the reactor temperature below 80°C. After feeding is complete, maintain the reaction at 80°C for 2.5 hours.
[0055] (2) Hydrolysis reaction:
[0056] Add 2.0% of deionized water to the above esterification product and stir continuously at 70°C for 1.0 hour to hydrolyze the pyrophosphate and polyphosphate in the system into a mixture of monoester and diester monomers.
[0057] (3) Neutralization reaction:
[0058] The system was cooled to 45°C, and monoethanolamine (MEA) was slowly added dropwise using a metering pump while monitoring the pH value of the system until the pH reached 6.5. After the reaction solution was cooled to room temperature, a light yellow, transparent, viscous liquid was obtained, which was an ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt.
[0059] Preparation Example 2:
[0060] This preparation example provides a method for preparing a water-soluble tribochemical extreme pressure agent (ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt), comprising the following steps:
[0061] (1) Esterification reaction:
[0062] 3.0 mol equivalents of isotridecyl alcohol polyoxyethylene ether (average ethylene oxide addition number EO=3) were placed in a reactor and heated to 65°C. Under nitrogen protection and constant stirring, 1.0 mol equivalents of phosphorus pentoxide (…) were slowly added in four batches. Control the feeding rate to maintain the reactor temperature below 82°C. After feeding is complete, maintain the reaction at 82°C for 2.75 hours.
[0063] (2) Hydrolysis reaction:
[0064] Add 2.5% deionized water (by mass of total material) to the above esterification product and continuously stir and hydrolyze at 75°C for 1.0 hour to convert the pyrophosphate and polyphosphate in the system into a mixture of monoester and diester monomers.
[0065] (3) Neutralization reaction:
[0066] The system was cooled to 48°C, and monoethanolamine (MEA) was slowly added dropwise using a metering pump while monitoring the pH value of the system until the pH reached 7.0. After the reaction solution was cooled to room temperature, a light yellow, transparent, viscous liquid was obtained, which was an ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt.
[0067] Preparation Example 3:
[0068] This preparation example provides a method for preparing a water-soluble tribochemical extreme pressure agent (ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt), comprising the following steps:
[0069] (1) Esterification reaction:
[0070] 3.0 mol equivalents of isotridecyl alcohol polyoxyethylene ether (average ethylene oxide addition number EO=3) were placed in a reaction vessel and heated to 70°C. Under nitrogen protection and constant stirring, 1.0 mol equivalents of phosphorus pentoxide (…) were slowly added in four batches. Control the feeding rate to maintain the reactor temperature below 85°C. After feeding is complete, maintain the reaction at 85°C for 3.0 hours.
[0071] (2) Hydrolysis reaction:
[0072] Add 3.0% of deionized water by mass to the above esterification product and continuously stir and hydrolyze at 80°C for 1.0 hour to convert the pyrophosphate and polyphosphate in the system into a mixture of monoester and diester monomers.
[0073] (3) Neutralization reaction:
[0074] The system was cooled to 50°C, and monoethanolamine (MEA) was slowly added dropwise using a metering pump while monitoring the pH value of the system until the pH reached 7.5. After the reaction solution was cooled to room temperature, a light yellow, transparent, viscous liquid was obtained, which was an ashless isomeric alcohol polyoxyethylene ether phosphate monoethanolamine salt.
[0075] Examples 1-3:
[0076] Example 1:
[0077] This embodiment provides a chipless rotary forging process for the drill tip of a screw tail, including the following steps:
[0078] (1) Formulation of synergistic reaction type water-based lubricating composition:
[0079] Add the remaining deionized water to a reaction vessel equipped with a constant temperature water bath and mechanical stirrer, and heat and maintain the temperature to 45°C. Turn on the stirrer and set the speed to 150 rpm. Add 5.0% boric acid powder and 1.5% D-tartaric acid by mass of the total mass in sequence, and continue stirring for 30 minutes until the powder is completely dissolved and the system is a transparent acidic solution.
[0080] Slowly pump 15.0% (by mass) of polyethylene glycol (PEG-400) into the base solution, followed by 3.0% (by mass) of a water-soluble tribochemical extreme pressure agent (obtained from Preparation Example 1). Increase the stirring speed to 300 rpm and shear mix for 20 minutes.
[0081] Triethanolamine was slowly added dropwise using an automatic titration device at 45°C with continuous stirring. The pH of the solution was monitored in real time using an online glass electrode. The addition was stopped when the pH stabilized precisely at 8.2, and the solution was kept at this temperature and allowed to stand for 15 minutes to obtain a water-based lubricating fluid with a loose coordination state.
[0082] (2) Feeding and pretreatment of metal wire:
[0083] 10B21 carbon steel wire is selected, and after the surface oxide scale is removed by the shelling machine, it enters the ultrasonic cleaning tank (deionized water medium, water temperature 40℃, ultrasonic frequency 28kHz, residence time 3 seconds), and then is sent to the rotary forging machine table by the roller traction system at a continuous feed speed of 10m / min.
[0084] (3) Dynamic temperature-controlled pre-application and in-situ gelation:
[0085] The lubricating composition obtained in step (1) is preheated to 60°C by an inline heater in the pipeline and then conveyed to an annular atomizing nozzle array located 15cm in front of the inlet of the rotary forging die. The atomizing gas pressure is controlled at 0.2MPa so that the composition is uniformly wetted on the surface of the moving wire.
[0086] The wire then passes through a high-frequency induction heating coil (induction frequency 30kHz) surrounding it. By adjusting the output power of the induction heating, the surface of the wire is rapidly heated to 110°C within 0.5 seconds. An annular air knife is installed at the outlet of the induction coil, with the compressed air pressure set to 0.3MPa and the airflow direction at a 45° angle to the direction of wire travel. This instantly blows away the water vapor that flashes onto the surface of the wire, driving the liquid film adhering to the metal interface to undergo in-situ supramolecular gelation from the inside out, forming a high-viscosity semi-solid pre-coated film.
[0087] (4) Chipless rotary forging of drill tip:
[0088] The wire pre-coated with a gel film continuously enters a four-lobed rotary forging die. The spindle speed of the die is set to 300 rpm, and the radial forging frequency of the die on the wire is controlled at 2000 times / min, extruding and forming the drill tip structure at the tail of the screw.
[0089] (5) Cooling and weakly alkaline degreasing and cleaning after molding:
[0090] After rotary forging, the screw drill tip is cooled to below 50°C by natural air cooling and then falls into a cleaning tank. It is then soaked and rinsed for 3 minutes at 50°C using a conventional weak alkaline water-based cleaning agent with a mass fraction of 2% (pH 9.0), followed by rinsing with deionized water and hot air drying to obtain a chip-free rotary forged screw tail drill tip.
[0091] Example 2:
[0092] This embodiment provides a chipless rotary forging process for the drill tip of a screw tail, including the following steps:
[0093] (1) Formulation of synergistic reaction type water-based lubricating composition:
[0094] Add the remaining deionized water to a reaction vessel equipped with a constant temperature water bath and mechanical stirrer, and heat and maintain the temperature to 48°C. Turn on the stirrer and set the speed to 175 rpm. Add 6.5% boric acid powder and 1.75% D-tartaric acid by mass of the total mass in sequence, and continue stirring for 35 minutes until the powder is completely dissolved and the system is a transparent acidic solution.
[0095] Slowly pump 17.5% (by mass) of polyethylene glycol (PEG-400) into the base solution, followed by 4.0% (by mass) of a water-soluble tribochemical extreme pressure agent (obtained from Preparation Example 2). Increase the stirring speed to 350 rpm and shear mix for 25 minutes.
[0096] Triethanolamine was slowly added dropwise using an automatic titration device at 48°C with continuous stirring. The pH of the solution was monitored in real time using an online glass electrode. The addition was stopped when the pH value stabilized precisely at 8.35. The solution was then kept at this temperature and allowed to stand for 15 minutes to obtain a water-based lubricating fluid with a loose coordination state.
[0097] (2) Feeding and pretreatment of metal wire:
[0098] 304 stainless steel wire is selected, and after the surface oxide scale is removed by the shelling machine, it enters the ultrasonic cleaning tank (deionized water medium, water temperature 45℃, ultrasonic frequency 28kHz, residence time 4 seconds), and then is sent to the rotary forging machine table by the roller traction system at a continuous feed speed of 12m / min.
[0099] (3) Dynamic temperature-controlled pre-application and in-situ gelation:
[0100] The lubricating composition obtained in step (1) is preheated to 62°C by an inline heater in the pipeline and then conveyed to an annular atomizing nozzle array located 18cm in front of the inlet of the rotary forging die. The atomizing gas pressure is controlled at 0.3MPa so that the composition is uniformly wetted on the surface of the moving wire.
[0101] The wire then passes through a high-frequency induction heating coil (induction frequency 40kHz) surrounding it. By adjusting the output power of the induction heating, the surface of the wire is rapidly heated to 115°C within 0.8 seconds. An annular air knife is installed at the outlet of the induction coil, with the compressed air pressure set to 0.4MPa and the airflow direction forming a 50° angle with the direction of wire travel. This instantly blows away the water vapor that flashes onto the surface of the wire, driving the liquid film adhering to the metal interface to undergo in-situ supramolecular gelation from the inside out, forming a high-viscosity semi-solid pre-coated film.
[0102] (4) Chipless rotary forging of drill tip:
[0103] The wire pre-coated with a gel film continuously enters a four-lobed rotary forging die. The spindle speed of the die is set to 400 rpm, and the radial forging frequency of the die on the wire is controlled at 3000 times / min, extruding and forming the drill tip structure at the tail of the screw.
[0104] (5) Cooling and weakly alkaline degreasing and cleaning after molding:
[0105] After being rotary forged, the screw drill tip is cooled to below 50°C by natural air cooling and then falls into a cleaning tank. Using a conventional weak alkaline water-based cleaning agent with a mass fraction of 2.5% (pH 9.5), it is soaked or sprayed for 4 minutes at 55°C, then rinsed with deionized water and dried with hot air to obtain a chip-free rotary forged screw tail drill tip.
[0106] Example 3:
[0107] This embodiment provides a chipless rotary forging process for the drill tip of a screw tail, including the following steps:
[0108] (1) Formulation of synergistic reaction type water-based lubricating composition:
[0109] Add the remaining deionized water to a reaction vessel equipped with a constant temperature water bath and mechanical stirrer, and heat and maintain the temperature to 50°C. Turn on the stirrer and set the speed to 200 rpm. Add boric acid powder (8.0% by mass) and D-tartaric acid (2.0% by mass) sequentially, and continue stirring for 45 minutes until the powder is completely dissolved and the system is a transparent acidic solution.
[0110] Slowly pump 20.0% (by mass) of polyethylene glycol (PEG-400) into the base solution, followed by 5.0% (by mass) of a water-soluble tribochemical extreme pressure agent (obtained from Preparation Example 3). Increase the stirring speed to 400 rpm and shear mix for 30 minutes.
[0111] Triethanolamine was slowly added dropwise using an automatic titration device at 50°C with continuous stirring. The pH of the solution was monitored in real time using an online glass electrode. The addition was stopped when the pH value stabilized precisely at 8.5. The solution was then kept at this temperature and allowed to stand for 15 minutes to obtain a water-based lubricating fluid with a loose coordination state.
[0112] (2) Feeding and pretreatment of metal wire:
[0113] 304 stainless steel wire is selected, and after the surface oxide scale is removed by the shelling machine, it enters the ultrasonic cleaning tank (deionized water medium, water temperature 50℃, ultrasonic frequency 28kHz, residence time 5 seconds), and then is sent to the rotary forging machine table by the roller traction system at a continuous feed speed of 15m / min.
[0114] (3) Dynamic temperature-controlled pre-application and in-situ gelation:
[0115] The lubricating composition obtained in step (1) is preheated to 65°C by an inline heater in the pipeline and then conveyed to an annular atomizing nozzle array located 20cm in front of the inlet of the rotary forging die. The atomizing gas pressure is controlled at 0.4MPa so that the composition is uniformly wetted on the surface of the moving wire.
[0116] The wire then passes through a high-frequency induction heating coil (induction frequency 50kHz) surrounding it. By adjusting the output power of the induction heating, the surface of the wire is rapidly heated to 120°C within 1.0 second. An annular air knife is installed at the outlet of the induction coil, with the compressed air pressure set to 0.5MPa and the airflow direction forming a 60° angle with the direction of wire movement. This instantly blows away the water vapor that flashes onto the surface of the wire, driving the liquid film adhering to the metal interface to undergo in-situ supramolecular gelation from the inside out, forming a high-viscosity semi-solid pre-coated film.
[0117] (4) Chipless rotary forging of drill tip:
[0118] The wire pre-coated with a gel film continuously enters a four-lobed rotary forging die. The spindle speed of the die is set to 500 rpm, and the radial forging frequency of the die on the wire is controlled at 4000 times / min, extruding and forming the drill tip structure at the tail of the screw.
[0119] (5) Cooling and weakly alkaline degreasing and cleaning after molding:
[0120] After rotary forging, the screw drill tip is cooled to below 50°C by cold air blowing and then falls into a cleaning tank. Using a conventional weak alkaline water-based cleaning agent with a mass fraction of 3% (pH value 10.0), it is soaked or sprayed and rinsed at 60°C for 5 minutes, followed by rinsing with deionized water and drying with hot air to obtain a chip-free rotary forged screw tail drill tip.
[0121] Comparative Examples 1-4:
[0122] Comparative Example 1:
[0123] Compared with Example 2, the difference is that a commercially available sulfur-phosphorus type pure oil-based cutting fluid is used for lubrication instead of the lubricating composition of the present invention, and the dynamic temperature control pre-coating and in-situ gelation steps (i.e., no induction heating flash evaporation process) are omitted. The wire is directly entered into the rotary forging die for forming after room temperature spraying, and organic solvent cleaning is used afterwards. All other aspects are the same.
[0124] Comparative Example 2:
[0125] Compared with Example 2, the difference is that the high-frequency induction heating coil and air knife flash evaporation process in step (3) are omitted. Instead, the preheated lubricating composition is sprayed onto the surface of the wire and then directly enters the rotary forging die for forming without high-frequency induction dehydration treatment. All other aspects are the same.
[0126] Comparative Example 3:
[0127] Compared with Example 2, the difference is that boric acid powder is not added to the lubricating composition prepared in step (1), and the corresponding mass fraction is made up by deionized water, while the rest are the same.
[0128] Comparative Example 4:
[0129] Compared with Example 2, the difference is that D-tartaric acid is not added to the lubricating composition prepared in step (1), and triethanolamine is not used for pH titration (the system is kept naturally acidic). The corresponding mass fraction is made up by deionized water, and everything else is the same.
[0130] Test Examples 1-5:
[0131] Test Example 1:
[0132] Prepare samples of the lubricating compositions obtained in Examples 1 to 3 and Comparative Examples 2 and 4.
[0133] A rotational rheometer (equipped with a coaxial cylindrical test fixture) was used, with the test temperature set to 60℃ and the shear rate set to... The initial dynamic viscosity of each group of samples was measured and recorded.
[0134] A simulation test platform was constructed, including a medium-frequency induction heating coil and a compressed air knife. A 304 stainless steel test piece with dimensions of 150mm×50mm×2mm was taken, and after the surface was degreased, cleaned and dried, a lubricating composition was sprayed onto the surface of the test piece, controlling the liquid film thickness to be approximately 0.1mm.
[0135] The testing platform was turned on, and the surface of the substrate was heated to 115°C within 1 second using induction heating. Simultaneously, an air knife was activated to dehydrate the substrate. Once the dehydration process was complete, the residual semi-solid film on the metal surface was immediately scraped off.
[0136] The collected residues were placed in the parallel plate testing system of a rheometer, and their dynamic viscosity and shear yield stress after treatment were tested at 60°C. For Comparative Example 2 (non-induction flash dehydration process), a conventional oven was set to 115°C for an equivalent time to heat-dry the residues.
[0137] Take another stainless steel sample of the same specifications and repeat the film formation process of steps 3 and 4. Cool the sample to room temperature.
[0138] One hundred 1mm × 1mm grids were scribed on the film surface of the test block using a cross-cutting device, with the scratches penetrating the film layer to reach the substrate. After cleaning the surface with a soft brush, standard test tape was applied to the grid area, allowed to stand and compact for 5 minutes, and then quickly peeled off at a 180-degree angle. The degree of peeling off the grid area was observed, and the adhesion level of the film to the metal substrate was evaluated according to the AST MD3359 standard.
[0139] Table 1. Macroscopic physical properties and interfacial adhesion test results of the lubricating composition
[0140]
[0141] in conclusion:
[0142] Combining the data in Table 1 and the appendix Figure 1 The initial dynamic viscosity of Examples 1 to 3 ranged from 43.18 to 48.31 mPa·s. The low viscosity state confirmed that boric acid, D-tartaric acid, and polyethylene glycol formed a stable solvation coordination equilibrium in a weakly alkaline environment, ensuring that the fluid could effectively wet the microscopic rough structure of the metal surface. After induction heating and air knife blowing, the dynamic viscosity of the examples increased dramatically to 185.64–247.81 Pa·s, an increase of several thousand times, with shear yield stress between 86.2 and 107.5 Pa. This abrupt change in viscosity directly verified that after the water molecules in the liquid film were forcibly stripped, the boron-tartaric acid complex and the polyether carrier underwent supramolecular-level hydrogen bond self-assembly, transforming the system from a Newtonian fluid into a high-viscosity gel phase with shear thickening properties.
[0143] As attached Figure 2 As shown, in the adhesion test, Examples 1 to 3 all achieved a 5B level, with smooth edges and no square peeling. Combined with the data analysis of Comparative Example 2, Comparative Example 2, lacking high-frequency induction heating from the inside out, used conventional external drying and dehydration, resulting in a viscosity of only 18.42 Pa·s and an adhesion level reduced to 2B. This indicates that external heat source heating causes preferential skinning on the liquid film surface, hindering internal moisture evaporation and preventing the formation of a uniform and tightly bound polymeric entanglement structure. Because the dehydration driving force is opposite to the metal interface, the physicochemical bonding between the residual film and the substrate is extremely weak. Comparative Example 4 lacks a multi-component organic acid complexing agent and pH buffer adjustment, resulting in significant heterogeneous agglomeration after treatment, leading to stress concentration and rapid deterioration of adhesion (1B). These test results objectively demonstrate from both rheological and interface engineering perspectives that the coupling of the chemical formulation and the skin effect heating mechanism of this invention can indeed achieve in-situ supramolecular gelation, providing a foundation for extreme pressure response under subsequent extreme conditions.
[0144] Test Example 2:
[0145] The semi-solid gel residues of Examples 1 to 3 and Comparative Example 3 that had been pretreated with induction heating at 115°C and dehydration by air knife were collected and placed in a desiccator to cool to room temperature.
[0146] Weigh the pulverized gel residue samples from each group, with the mass controlled between 8.5 and 10.2 mg, and spread them evenly in an alumina ceramic crucible.
[0147] The crucible was moved into the heating chamber of the synchronous thermal analyzer, and a reference empty crucible was placed there.
[0148] The test system was set to use high-purity nitrogen as a protective gas, with the gas flow rate controlled at 50 mL / min.
[0149] Set the instrument temperature program: the initial temperature is 25℃, and the temperature is heated to 600℃ at a constant heating rate of 10℃ / min. Thermogravimetric (TGA) and differential scanning calorimetry (DSC) signals are acquired synchronously throughout the process.
[0150] After the test, the mass loss rate and heat flow curve data of each sample were exported, and the characteristic endothermic peak temperature, weight loss range and final residual mass were extracted and calculated.
[0151] Table 2. Results of TGA-DSC thermal analysis of gel residues from lubricating compositions.
[0152]
[0153] Note: "-" indicates no data or that the substance does not exist.
[0154] in conclusion:
[0155] Combining the data in Table 2 and the appendix Figure 3 and attached Figure 4 Examples 1 to 3 exhibit a clear endothermic peak in the organic phase degradation phase within the temperature range of 312.4℃ to 323.1℃, accompanied by a mass loss of 38.4% to 42.6%. Thermodynamic characteristics correspond to the depolymerization of organic segments and thermal degradation of the polyether skeleton within the spatial network structure formed in the lubricating film when the temperature exceeds 300℃ in the core extreme pressure zone of rotary forging. The depolymerization and degradation process absorbs the heat generated by the plastic deformation of the metal, alleviating the accumulation of thermal stress at the processing interface. When the temperature continues to rise to the range of 445.2℃ to 456.3℃, a clear high-temperature phase transition secondary endothermic peak is recorded on the DSC curves of Examples 1 to 3. At this point, the weight loss trend of the TGA curve slows significantly and tends to plateau, with the final residual mass percentage at 600℃ remaining at 15.3% to 20.4%. This secondary endothermic peak confirms that after the degradation of the spatial network structure, the encapsulated borate complex undergoes complete dehydration in a high-temperature environment and a phase transition occurs near 450℃, generating boron oxide (Boron(II) oxide) with glassy melting characteristics. This inorganic residue forms a glassy thin film with a layered structure at the high-temperature and extreme-pressure contact surface, providing an interlayer slip mechanism under extreme conditions.
[0156] Based on the data from Comparative Example 3, since the system in Comparative Example 3 does not contain boric acid powder, its organic phase degradation peak temperature is advanced to 305.8℃, and the mass loss rate in the main degradation stage is as high as 85.7%. In the high-temperature region exceeding 400℃, Comparative Example 3 did not show a phase transition endothermic peak, and the residual mass rate at 600℃ was only 1.2%. The data shows that the lubricating film lacking boric acid components undergoes complete thermal decomposition and burn-off in processing environments above 300℃, and cannot retain any solid residues that provide physical support. The comparative results thermodynamically verify the multi-level response mechanism of the formulation of this invention under different temperature gradients, namely, at medium and low temperatures, the high-viscosity gel network bears the extreme pressure, and at high temperatures, the in-situ generated borosilicate glassy molten phase provides anti-cold welding and continuous lubrication, meeting the lubrication requirements of the entire temperature range of metal forming processing.
[0157] Test Example 3:
[0158] The same four-lobed chipless rotary forging machine was selected, and 304 stainless steel wire of the same diameter and specifications from the same batch was used as the processing raw material.
[0159] For each group of individual tests, a brand-new tungsten steel rotary forging die with a consistent cavity surface finish was installed on the machine tool spindle.
[0160] Lubricating materials were prepared according to the methods and steps corresponding to Examples 1 to 3 and Comparative Examples 1 to 4, and the parameters of the liquid supply pipeline, the parameters of the heating module, and the spindle speed and feed rate of the machine tool were set.
[0161] The machine tool is started to continuously machine the drill tip at the end of the screw. During the machining process, the equipment vibration monitoring is activated simultaneously, and the output is manually sampled at regular intervals to measure the macroscopic dimensions.
[0162] When the machine tool produces abnormal operating noise, or the dimensions of continuously produced products exceed the set tolerance range, or when a stop inspection reveals macroscopic metal flakes adhering to the mold forming surface, the current mold processing is deemed to have failed and the test is immediately terminated.
[0163] Record the total number of qualified screws produced from the time the new mold is loaded until the machine is shut down due to failure. Clean the machine table and replace the mold for the next group of tests.
[0164] Table 3. Statistical Table of Total Number of Qualified Screws Produced Continuously by Chipless Rotary Forging Dies
[0165]
[0166] in conclusion:
[0167] Combining the data in Table 3 with the appendix Figure 5The total number of qualified screws processed in Examples 1 to 3 reached 84,512 to 98,741. This result verifies that the supramolecular gel film generated by phase inversion after induction heating and airflow dehydration of the water-based lubricating composition on the metal substrate surface possesses high-strength physical and chemical adhesion properties. Under high-frequency radial forging contact stress of 2 to 3 GPa, the high-viscosity semi-solid gel film maintains the integrity of the boundary lubrication layer by relying on the internal hydrogen bond network, avoiding being squeezed off by mechanical pressure. In the core region where the local temperature exceeds 300°C due to the intense plastic deformation of the metal, the borate complex encapsulated inside the lubricating film transforms into a borosilicate glass phase, generating a high-temperature molten inorganic film with shear slip properties in situ at the interface between the mold and the workpiece. This blocks the inter-atomic diffusion between metal atoms under high temperature and pressure, preventing cold welding and microcrack propagation of 304 stainless steel on the mold surface.
[0168] Analysis of the comparative data shows that Comparative Example 1, using commercially available pure oil-based cutting fluid without a dehydration phase change step, produced only 12,450 continuously processed parts. The oil-based extreme pressure additive relied on physical adsorption to form a film on the metal surface. Under extreme contact stress and high-frequency forging, this film ruptured and was rapidly expelled from the processing area, causing delamination lubrication, leading to direct metal contact and rapid, severe cold welding. Comparative Example 2, using a water-based fluid without heating and flash evaporation, produced 15,328 processed parts. Low-viscosity fluids without timely water removal cannot undergo coordination bond recombination and supramolecular self-assembly at the interface, resulting in low film cohesion and interface anchoring, leading to collapse during the initial compression stage of processing. Comparative Example 3, lacking boric acid, produced 34,105 processed parts. Although a supramolecular polymer network supported stress in the early stages of extreme pressure processing, as the temperature in the extreme pressure zone increased, the organic chain segments thermally decomposed, preventing the system from generating an inorganic glassy framework with high-temperature load-bearing support. This resulted in the mold surface losing protection and experiencing rapid wear at high temperatures. Comparative Example 4, lacking multi-component organic acid complexation and pH buffering, saw a decrease in the number of processed parts to 21,876. The presence of incompletely dissolved microcrystalline structures and heterogeneous aggregates within the fluid system disrupted the continuity and uniformity of the macroscopic coating of the gel film, making it highly susceptible to boundary film rupture and detachment at defect concentration points under high-frequency forging stress. Test data, from the perspective of actual engineering processing life, confirms that the coupling effect of the in-situ gel phase transition mechanism and the high-temperature stepped physical phase transition mechanism indeed improves the wear resistance limit of the chipless forming die.
[0169] Test Example 4:
[0170] The machine tool processing batch size was set at 10,000 pieces. During the continuous processing of screws in each group (Examples 1 to 3 and Comparative Examples 1 to 4), all finished products produced in that batch were collected independently.
[0171] The collected finished products were placed in an ultrasonic cleaning tank and cleaned for 15 minutes at 50°C using a conventional alkaline cleaning agent to remove residual oil, metal shavings, and lubricating film residue from the surface. They were then dried with hot air.
[0172] High-precision vernier calipers were used to measure the key geometric dimensions of the drill tee area. A full inspection was performed on the cleaned finished product, visually examining the drill tip surface for macroscopic tears, cracks, missing material, or obvious metal spalling defects.
[0173] Count the number of defective products with out-of-tolerance dimensions or macroscopic surface defects in each batch, and calculate and record the defect rate percentage for each batch.
[0174] 35 pieces are randomly selected from each set of qualified products as roughness test samples and fixed on a special V-shaped fixture.
[0175] A mechanical stylus-type surface roughness meter was used to perform contact scanning measurements on the working surface of the drill tip of the samples. The stylus measurement stroke was set to 0.8 mm and the sampling length to 0.25 mm. The average surface roughness (Ra) value of each sample was recorded.
[0176] Calculate and record the arithmetic mean of the Ra values for each of the 35 samples in the group.
[0177] Table 4. Statistics on Macroscopic Forming Quality and Yield of Finished Drill Tips Produced by Chipless Rotary Forging
[0178]
[0179] in conclusion:
[0180] Combining the data in Table 4 and the appendix Figure 6 In Examples 1 to 3, the defect rate was controlled at an extremely low level of 0.29% to 0.47%, while the average surface roughness Ra value of the finished drill tips remained between 0.69 and 0.82 μm. This demonstrates that the in-situ formation of polymer entanglement structures after induction heating and blow-drying dehydration creates a continuous and uniform boundary protective layer between the microscopic roughness peaks on the metal surface. Under high-frequency, high-pressure extrusion at 2–3 GPa, this high-viscosity gel film exhibits excellent shear thickening characteristics, effectively dispersing the concentrated stress between the mold and the metal substrate, and improving the plastic flow behavior of 304 stainless steel within the mold cavity. Uniform deformation of the material prevents surface tearing and microcrack formation. With the increase of local instantaneous temperature, the boron oxide glassy molten phase generated within the system provides a low-shear-strength slip interface, significantly reducing the interfacial friction coefficient, thereby significantly improving the smoothness and dimensional stability of the metal forming surface.
[0181] Based on the comparative data, Comparative Example 1, using commercially available pure oil-based cutting fluid, saw a defect rate soar to 8.94%, with an Ra value as high as 3.45 μm. The purely physically adsorbed oil film ruptured under extreme contact stress, causing direct friction and cold welding on the metal surface, resulting in forced tearing of the material and leaving deep scratches and defects on the surface. Comparative Example 2, using a water-based fluid but without heating and flash evaporation treatment, had a low cohesive liquid film that could not resist forging and extrusion. Interfacial lubrication failure led to uneven plastic deformation, resulting in a defect rate of 6.12%. Comparative Example 3, lacking boric acid components, saw its organic lubricating film ablated in the high-temperature section of the extreme pressure zone. The interface lost its anti-wear support skeleton, exacerbating direct dry friction between the metal and the mold, leading to an Ra value of 1.94 μm on the formed surface. Comparative Example 4, lacking an organic acid complexing agent and a pH buffer system, experienced heterogeneous agglomeration within the lubricating fluid, resulting in inconsistent film thickness and density. Under localized high pressure, the weakest areas experienced film collapse first, leading to stress concentration and localized tearing on the surface, resulting in a defect rate of 5.63%. This test data objectively confirms the coupled application of the skin effect-induced heating-induced abrupt change in rheological dynamics and the multi-stage extreme pressure response mechanism. This overcomes the limitations of traditional oil- and water-based lubricants under extreme conditions, effectively ensuring the surface quality and batch production stability of high-strength metal forming processes from a macroscopic perspective.
[0182] Test Example 5:
[0183] 200 finished screws each from Examples 1 to 3 and Comparative Example 1 were collected as test samples.
[0184] Prepare a 3% (w / w) weakly alkaline water-based cleaning solution with a pH value controlled between 8.5 and 9.0.
[0185] Place the sample in the cleaning tank, set the cleaning solution temperature to 55℃, and turn on the ultrasonic cleaning for 10 minutes to remove grease.
[0186] Remove the sample and sonicate it in deionized water for 3 minutes, then dry it in a hot air drying oven at 80°C.
[0187] The surface residue was assessed using the standard extraction-weighing method. Fifty pieces were randomly selected from each group of cleaned samples and immersed in a beaker containing an equal volume of chromatographic grade n-hexane and anhydrous ethanol, and ultrasonically extracted for 20 minutes.
[0188] The extract was transferred to a pre-weighed evaporating dish, and the solvent was evaporated in a water bath. The residue was then dried in a vacuum drying oven to constant weight. The mass of the residue was measured using a microbalance with an accuracy of 0.01 mg. The mass of residue per unit area for each group was calculated based on the total surface area of the 50 samples.
[0189] Fifteen pieces were randomly selected from the remaining qualified cleaned products in each group and fixed on the stage of the optical contact angle measuring instrument. 2 μL of deionized water was dropped onto the screw-shaped surface using a micro-syringe.
[0190] Record the side image of the droplet after it has been in contact with the surface for 5 seconds, and calculate the contact angle of the water droplet on the surface using software fitting. Take the arithmetic mean of the test results of 15 samples as the contact angle data for this group.
[0191] Table 5. Results of Degreasing and Cleaning Residue Rate and Surface Contact Angle Tests on Molded Products
[0192]
[0193] in conclusion:
[0194] Combining the data in Table 5 and the appendix Figure 7 and attached Figure 8 After undergoing the same weakly alkaline water-based cleaning process, Examples 1 to 3 maintained a residue mass per unit area of [missing information]. In the lower range, the water droplet contact angle on the test surface ranged from 22.7° to 29.1°. The residue mass of Comparative Example 1 was as high as... The water droplet contact angle reached 82.3°. These two sets of data reflect the essential differences in the interfacial chemical state of different lubrication systems after molding.
[0195] The all-water-based supramolecular system of this invention consists of water-soluble polyethers, polyhydroxy compounds, and borate complexes formed from multi-component organic acids. Under the high-temperature and extreme-pressure environment of the processing core area, some organic segments undergo thermal degradation, accompanied by a phase transition of the borate to a borosilicate glass phase. The residual products are mainly low-molecular-weight polar fragments and water-soluble inorganic borides. In a weakly alkaline water-based cleaning solution, these surface residues can rapidly undergo hydrolysis, decomplexation, and polar solvation reactions, desorbing from the metal substrate surface and dissolving and dispersing in the aqueous phase. The cleaned 304 stainless steel surface has its physical coating removed, exposing a high metal surface energy and exhibiting an extremely low water droplet contact angle. This verifies that parts processed using the method of this invention possess the interface cleanliness to directly proceed to subsequent coating, electroplating, or passivation processes.
[0196] Comparative Example 1 uses a traditional pure oil-based cutting fluid. The system contains a large amount of non-polar mineral base oil and sulfur-phosphorus extreme pressure additives, which undergo carbonization and polymerization reactions under localized high temperature and high-frequency forging. The resulting hydrophobic carbon chain residues and reactive boundary friction films that form strong chemical bonds with the metal matrix are difficult to remove by conventional weakly alkaline aqueous emulsification. The large amount of hydrophobic organic residues remaining on the surface leads to a high water droplet contact angle, which in industrial production typically requires the introduction of volatile organic solvents or high-concentration strong alkaline solutions for energy-intensive secondary degreasing. Test results, from the perspective of post-processing, confirm that the composite gel system of this invention, while meeting the anti-wear requirements under extreme working conditions, completely eliminates the stubborn cleaning burden caused by oil-based processing, achieving a green water-based approach for the entire metal processing and degreasing / cleaning process.
Claims
1. A chipless rotary forging process for the drill tip of a screw tail, characterized in that, Includes the following steps: Deionized water was heated, boric acid powder and D-tartaric acid were added, and the mixture was stirred at a constant temperature. Polyethylene glycol and water-soluble tribochemical extreme pressure agent were added, and the stirring speed was increased to perform shear mixing. Triethanolamine was added dropwise under continuous stirring until the pH of the solution stabilized. The mixture was then kept warm and allowed to stand to obtain a water-based lubricating composition. The metal wire with the surface oxide scale removed is cleaned in an ultrasonic cleaning tank and then sent to the rotary forging machine. The water-based lubricating composition is preheated and then sprayed onto the surface of the moving metal wire through an array of atomizing nozzles. The metal wire passes through a high-frequency induction heating coil to heat the surface of the metal wire, and an annular air knife located at the outlet of the high-frequency induction heating coil blows across the surface of the metal wire to form a high-viscosity semi-solid pre-coated film on the surface of the metal wire. The metal wire pre-coated with the high-viscosity semi-solid pre-coated film enters the rotary forging die of the rotary forging machine and is rotary forged to form a screw tail drill tip structure. The screw tail drill tip structure after rotary forging is cooled down, cleaned in a weakly alkaline water-based cleaning agent, rinsed and dried with hot air.
2. The chipless rotary forging process according to claim 1, characterized in that, In the step of obtaining the water-based lubricating composition, the deionized water is heated to 45°C to 50°C; The added boric acid powder accounts for 5.0% to 8.0% of the total mass of the water-based lubricating composition, and the added D-tartaric acid accounts for 1.5% to 2.0% of the total mass of the water-based lubricating composition. The constant temperature stirring time is 30 to 45 minutes, and the constant temperature stirring speed is set to 150 rpm to 200 rpm; The added polyethylene glycol accounts for 15.0% to 20.0% of the total mass of the water-based lubricating composition, and the added water-soluble tribochemical extreme pressure agent accounts for 3.0% to 5.0% of the total mass of the water-based lubricating composition. The shearing and mixing time is 20 to 30 minutes, and the stirring speed is increased to 300 rpm to 400 rpm; The pH value of the solution remained stable at 8.2–8.5; The time for keeping it warm and still is 15 to 30 minutes.
3. The chipless rotary forging process according to claim 1, characterized in that, The preparation steps of the water-soluble tribochemical extreme pressure agent include: 3.0 mol equivalents of isotridecyl alcohol polyoxyethylene ether with an average ethylene oxide addition number of 3 were heated to 60℃~70℃. Under nitrogen protection and constant stirring, 1.0 mol equivalents of phosphorus pentoxide were added in batches. The temperature of the reactor was controlled within the range of 80℃~85℃. After the addition was completed, the reaction was kept at the temperature for 2.5~3.0 hours to obtain the esterification reaction product. Add 2.0% to 3.0% of deionized water by mass of the total material to the esterification reaction product, and continuously stir and hydrolyze at 70°C to 80°C for 1.0 hour; Cool the mixture to 45℃~50℃ and add monoethanolamine dropwise until the pH of the mixture reaches 6.5~7.
5.
4. The chipless rotary forging process according to claim 1, characterized in that, The water-soluble tribochemical extreme pressure agent is an ashless alcohol ether phosphate alcohol amine salt; The average molecular weight of the polyethylene glycol is 200 to 600.
5. The chipless rotary forging process according to claim 1, characterized in that, In the step of sending the metal wire with the surface oxide scale removed to the rotary forging machine after being cleaned in the ultrasonic cleaning tank, the metal wire is selected as 10B21 carbon steel wire or 304 stainless steel wire. The ultrasonic cleaning tank uses deionized water as the medium, the water temperature is controlled at 40℃~50℃, the ultrasonic frequency is set at 25kHz~40kHz, and the metal wire stays in the ultrasonic cleaning tank for 3~5 seconds. The cleaned metal wire is fed to the rotary forging machine via a roller traction system, with the continuous feed speed set to 10m / min to 15m / min.
6. The chipless rotary forging process according to claim 1, characterized in that, In the step of forming the high-viscosity semi-solid pre-coated film, the water-based lubricating composition is preheated to 60°C to 65°C; The atomizing nozzle array is located 15cm to 20cm in front of the inlet of the rotary forging die; The atomizing gas pressure of the atomizing nozzle array is controlled between 0.2 MPa and 0.4 MPa.
7. The chipless rotary forging process according to claim 1, characterized in that, In the step of forming the high-viscosity semi-solid pre-coated film, the induction frequency of the high-frequency induction heating coil is 30kHz to 50kHz. The surface of the metal wire is heated to 110°C to 120°C within 0.5 to 1.0 seconds.
8. The chipless rotary forging process according to claim 1, characterized in that, In the step of forming the high-viscosity semi-solid pre-coated film, the compressed air pressure of the annular air knife is set to 0.3MPa to 0.5MPa, and the airflow direction discharged from the annular air knife forms an angle of 45° to 60° with the forward direction of the metal wire.
9. The chipless rotary forging process for the drill tip of a screw tail according to claim 1, characterized in that, In the step of rotary forging the drill tip structure at the tail of the screw, the rotary forging die is a four-lobed rotary forging die; The spindle speed of the rotary forging die is set to 300 rpm to 500 rpm; The radial forging frequency of the metal wire is controlled at 2000-4000 times / min by the rotary forging die.
10. The chipless rotary forging process according to claim 1, characterized in that, In the steps of cleaning in the weakly alkaline water-based cleaning agent, rinsing and hot air drying, the drill tip structure at the screw tail is cooled to below 50°C. The weakly alkaline water-based cleaning agent has a mass fraction of 2% to 3% and a pH value of 9.0 to 10.0; The cleaning temperature is 50℃~60℃, and the cleaning time is 3~5 minutes; Cleaning methods include soaking and rinsing or spray rinsing.